The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/1078-0432.ccr-15-1714
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Negative Status is Associated with Lower Mutation Burden, Differential Expression of Immune-Related Genes, and Worse Survival in Stage III Melanoma

Abstract: Purpose: Understanding why some melanomas test negative for PD-L1 by IHC may have implications for the application of anti-PD-1 therapies in melanoma management. This study sought to determine somatic mutation and gene expression patterns associated with tumor cell PD-L1 expression, or lack thereof, in stage III metastatic melanoma to better define therapeutically relevant patient subgroups.Experimental Design: IHC for PD-L1 was assessed in 52 American Joint Committee on Cancer stage III melanoma lymph node sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 40 publications
6
76
2
Order By: Relevance
“…Our analysis suggests that combinations of anti-PD-1/PD-L1/CTLA4-blocking antibodies can induce responses regardless of the TMB level. This observation is supported by prior studies reporting that combined ipilimumab and nivolumab produced similar response rates in PD-L1-expressing and non-expressing tumors,(49) which is relevant because increased PD-L1 expression correlates with higher TMB(50). The number of patients treated with combination therapy was, however, small in our study, and the implications of TMB level for combination therapy requires validation in larger cohorts.…”
Section: Discussionsupporting
confidence: 81%
“…Our analysis suggests that combinations of anti-PD-1/PD-L1/CTLA4-blocking antibodies can induce responses regardless of the TMB level. This observation is supported by prior studies reporting that combined ipilimumab and nivolumab produced similar response rates in PD-L1-expressing and non-expressing tumors,(49) which is relevant because increased PD-L1 expression correlates with higher TMB(50). The number of patients treated with combination therapy was, however, small in our study, and the implications of TMB level for combination therapy requires validation in larger cohorts.…”
Section: Discussionsupporting
confidence: 81%
“…Mutation load has been shown to correlate with response to anti-PD1 immunotherapy [22]. Rizvi et al performed whole exome sequencing of non-small cell lung cancers treated with pembrolizumab and showed that higher mutation load correlated with better response rate (63% vs 0%), more durable clinical benefit (73% vs 13%), and better progression-free survival (14.5 vs 3.7 months)[23].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermutated tumors with more than 500 SNVs showed obviously higher PD-L1 expression than tumors with low mutation. The specific co-rrelation of PD-L1 expression with high mutations has been reported, and PD-L1 expression may be one parameter responsible for good responses in the clinic to anti-immune checkpoint antibody therapy (12). In the future, the immune-response gene profiling of hypermutated tumors should be performed to identify better biomarkers to predict good responders to antibody treatment.…”
Section: Discussionmentioning
confidence: 99%